2013
DOI: 10.1037/a0030463
|View full text |Cite
|
Sign up to set email alerts
|

Attention orienting by gaze and facial expressions across development.

Abstract: Processing of facial expressions has been shown to potentiate orienting of attention toward the direction signaled by gaze in adults, an important social-cognitive function. However, little is known about how this social attention skill develops. This study is the first to examine the developmental trajectory of the gaze orienting effect (GOE), its modulations by facial expressions, and its links with theory of mind (ToM) abilities. Dynamic emotional stimuli were presented to 222 participants (7-25 years old) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

21
75
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 44 publications
(97 citation statements)
references
References 81 publications
(186 reference statements)
21
75
1
Order By: Relevance
“…Indeed, although fast attention orienting toward the direction of another's gaze is expected regardless of facial expression, orienting to an object eliciting fear should be even faster, given that the object being looked-at is likely to be a threat. In accordance with this idea and with previous studies, we found an increased GOE for fearful compared to neutral faces (Fox et al, 2007;Graham et al, 2010;Mathews et al 2003;Neath et al, 2013;Tipples, 2006). As outlined in the introduction, failure by some studies to find such a GOE increase for fearful compared to neutral faces could be attributed to the use of a too short SOA (e.g., Bayless et al, 2011;Galfano et al, 2011), the use of a static rather than dynamic cue (e.g., Hietanen & Leppanen, 2003), or the use of a discrimination task rather than a localization task (e.g., Mathews et al 2003 in low anxious; Holmes et al, 2010).…”
Section: Goe Modulation By Emotionssupporting
confidence: 80%
See 4 more Smart Citations
“…Indeed, although fast attention orienting toward the direction of another's gaze is expected regardless of facial expression, orienting to an object eliciting fear should be even faster, given that the object being looked-at is likely to be a threat. In accordance with this idea and with previous studies, we found an increased GOE for fearful compared to neutral faces (Fox et al, 2007;Graham et al, 2010;Mathews et al 2003;Neath et al, 2013;Tipples, 2006). As outlined in the introduction, failure by some studies to find such a GOE increase for fearful compared to neutral faces could be attributed to the use of a too short SOA (e.g., Bayless et al, 2011;Galfano et al, 2011), the use of a static rather than dynamic cue (e.g., Hietanen & Leppanen, 2003), or the use of a discrimination task rather than a localization task (e.g., Mathews et al 2003 in low anxious; Holmes et al, 2010).…”
Section: Goe Modulation By Emotionssupporting
confidence: 80%
“…Most importantly, it allowed for testing the idea that anger can enhance the GOE compared to neutral faces when fear is not included in the design. At the behavioral level, in accordance with previous studies (Bayless et al, 2011;Holmes et al, 2006;Neath et al, 2013), we predicted that (i) relative to neutral faces, the GOE would be larger for fearful and surprised faces and (ii) angry faces would enhance the GOE compared to neutral and happy faces. Regarding ERP modulations, at target presentation, we expected to replicate the congruency effects on P1 and N1 components and predicted larger modulations of these effects for fearful, surprised, and angry expressions compared to neutral expressions, reflecting an enhancement of the early visual processing of the target for these emotions.…”
Section: Introductionsupporting
confidence: 72%
See 3 more Smart Citations